Penerapan Metode User Centered Design (UCD) Dalam Perancangan System Register BRI Document Management System - Arnan, Sefian; Meiriza, Allsela; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to design a user interface for the Brimen document borrowing/returning registration application by implementing the user centered design (UCD) method at PT. Bank Rakyat Indonesia (Persero), Tbk. Especially the A.rivai Palembang Branch. This destop application design was created because the customer document borrowing/returning registration system in the Brimen division is currently still done manually using an A5 book, this is considered not very effective and efficient because miscommunication often occurs when documents have been borrowed without registering, in addition, searching for the location of customer documents and storing register data still involves Microsoft Excel so that this system is still less flexible when operated by ADK officers or Brimen employees. By optimizing the user interface design, namely the User Interface through an approach using the User Centered Design (UCD) method, it is hoped that the designed application can provide a better user experience and support operational efficiency in managing Brimen customer debtor data archives. There are several phases including understanding the use of the application, analyzing user needs in depth, creating responsive design solutions, and continuous evaluation and testing. By carrying out these phases, researchers can find and solve existing problems and create user interface (UI) designs that respond to user expectations and desires. This test involved 10 users using the System Usability Scale (SUS) questionnaire. The results showed that the Brimen Customer/Debtor Document Register Destop Application obtained an average score of 76.5 on the SUS survey. This value illustrates good user satisfaction and the application design meets user needs. Therefore, the design of this application can provide an optimal experience that better meets user needs.